Menentukan Efektivitas Pemanfaatan Teknologi Pembelajaran Terhadap Motivasi Belajar Siswa di MAS Plus Darul Hufadz - Ade Rosadi; Partono Partono; Anggit Suryopratomo (Ma'soem University, 2022)
In teaching and learning activities, student learning motivation is very important and mandatory because it can encourage students to participate in teaching and learning activities curiously so that the learning atmosphere becomes conducive, learning objectives can be achieved and students have the expected value standards. The purpose of this study is to apply data mining in processing student value data to measure how far the influence of the use of technology in learning is on student learning motivation at MAS Plus darul Hufadz. The analysis used in this study consisted of the calculation of the highest and lowest values, mean, median, standard deviation and range in each research variable.